Comparative Genomic Analysis Reveals Ecological Differentiation in the Genus Carnobacterium - Iskandar, Christelle F.; Borges, Frédéric; Taminiau, Bernard; Daube, Georges; Zagorec, Monique; Remenant, Benoît; Leisner, Jørgen J.; Hansen, Martin A.; Sørensen, Søren J.; Mangavel, Cécile; Cailliez-Grimal, Catherine; Revol-Junelles, Anne-Marie (Frontiers in Microbiology, 2017)
Lactic acid bacteria (LAB) differ in their ability to colonize food and animal-associated habitats: while some species are specialized and colonize a limited number of habitats, other are generalist and are able to colonize multiple animal-linked habitats. In the current study, Carnobacterium was used as a model genus to elucidate the genetic basis of these colonization differences. Analyses of 16S rRNA gene meta-barcoding data showed that C. maltaromaticum followed by C. divergens are the most prevalent species in foods derived from animals (meat, fish, dairy products), and in the gut. According to phylogenetic analyses, these two animal-adapted species belong to one of two deeply branched lineages. The second lineage contains species isolated from habitats where contact with animal is rare. Genome analyses revealed that members of the animal-adapted lineage harbor a larger secretome than members of the other lineage. The predicted cell-surface proteome is highly diversified in C. maltaromaticum and C. divergens with genes involved in adaptation to the animal milieu such as those encoding biopolymer hydrolytic enzymes, a heme uptake system, and biopolymer-binding adhesins. These species also exhibit genes for gut adaptation and respiration. In contrast, Carnobacterium species belonging to the second lineage encode a poorly diversified cell-surface proteome, lack genes for gut adaptation and are unable to respire. These results shed light on the important genomics traits required for adaptation to animal-linked habitats in generalist Carnobacterium.